2015
DOI: 10.1063/1.4938146
|View full text |Cite
|
Sign up to set email alerts
|

Experimental wave flume study of Savonius-type multiple rotor arrays

Abstract: An array of horizontal axis Savonius-type three-part rotors, each consisting of three blades, is designed and built in-house to conduct performance analysis experiments for a parallel tandem arrangement in a wave flume at different wave physical and positioning conditions. The experiments are performed at different wave heights, wave periods, and longitudinal spacings between the rotors, and their submergence positions are for a previously adjusted constant water depth. The power output and wave-to-mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…10 inch blade displaces large volume of water causes to reduce the rpm and leads to have lower momentum as compared with the 8 inch blade. Tutar and Veci [19] also observed that the rotational speed of the rotor influence the water wave height, in fact, higher rotational speed leads to have higher water wave height. However, the figure shows that the wave height gradually increases with the increase of the water depth.…”
Section: Investigation Of Wave Characteristics With Rotor Typementioning
confidence: 93%
See 1 more Smart Citation
“…10 inch blade displaces large volume of water causes to reduce the rpm and leads to have lower momentum as compared with the 8 inch blade. Tutar and Veci [19] also observed that the rotational speed of the rotor influence the water wave height, in fact, higher rotational speed leads to have higher water wave height. However, the figure shows that the wave height gradually increases with the increase of the water depth.…”
Section: Investigation Of Wave Characteristics With Rotor Typementioning
confidence: 93%
“…The flow around the rotor was studied with particle image velocimetry (PIV) measurements. Tutar and Veci [19] carried out experimental study on rotor type wave generator and found that placement of the rotor on the water surface and number of blades makes significant contribution on water wave energy. In another study Tutar and Veci [20] showed that the wave height and wave period along the submergible condition like shallow or deep water depth influence the wave energy conversion efficiency.…”
Section: Investigation Of Wave Characteristics With Rotor Typementioning
confidence: 99%